Sosialisasi Profil Pelajar Pancasila P5 Menjadi P7 Kebiasaan Anak Indonesia Hebat di SMA YP Unila - Yanzi, Hermi; Hariri, Hasan; Seftriyana, Elisa (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
This community service aims to socialize and internalize the values ​​of the Pancasila Student Profile (P5) in the daily lives of YP Unila Senior High School students through the development of the P7 concept, namely seven positive habits that reflect the character of great Indonesian children. This socialization activity was carried out as part of the school's efforts to support the strengthening of student character through the P7 program. The methods used included interactive lectures, group discussions, habit simulations, and joint reflection. The results of the study showed that the socialization of P5 into P7 Habits of Great Indonesian Children at YP Unila Senior High School was that teachers understood the transformation of P5 values ​​into seven main habits that students practiced. Thus, this activity was effective in strengthening the Pancasila Student Profile while facilitating the formation of positive habits among students.